(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe year-to-year changes (2021-2023) in demographics and outpatient visit volume at the Traditional Medicine Department, 7A Military Hospital, and to identify shifts in disease composition by ICD-10 chapters, with a focus on musculoskeletal disorders. Method: Retrospective, cross-sectional study of all 19.587 outpatient records from 1/2021 to 12/2023. Variables collected included age, sex, annual visit counts, ICD-10 diagnoses, and distributions by chapters/common codes. Descriptive analyses were performed; categorical variables were compared using the χ² test with p < 0.05. Results: Visit volume fell sharply in 2021 (4653), surged in 2022 (7636), and remained high in 2023 (7298). The proportion of patients aged 16-59 years increased significantly (p < 0.001). The disease profile shifted markedly toward Chapter XIII (diseases of the musculoskeletal system and connective tissue): from 68.04% (2021) to 77.45% (2022) and 89.65% (2023), while several other chapters declined. At the ICD-10 code level, M53.0 rose from 9.6% to 39.6%, N20.0 more than tripled; M53.1 decreased, whereas M54.4 maintained a high share. Conclusion: Post-COVID-19 saw outpatient morbidity reshaped, marked by rising musculoskeletal cases and more working-age patients, underscoring the need to prioritize resources and optimize musculoskeletal pain management in specialized traditional medicine services.